2020
DOI: 10.3390/app11010065
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Paper Sludge and Dendromass on Properties of Phytomass Pellets

Abstract: Woody and agricultural wastes are important fuels in many countries, and have the potential of being even more important in the future. The main problems of plant biomass combustion are low ash melting temperatures and increased emissions. The most widely used treatment to solve the problem of low ash melting point is blending a fuel with an additive. In this work, pellets were produced from wheat straw containing wood sawdust and paper sludge in the following proportions 40:40:20 and 45:45:10 (straw/sawdust/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…In general, the quality of these fuels is lower than wood biomass. The main problems are their low bulk density, high ash content, low ash melting temperatures, and low calorific values [5,6]. High ash content and low ash melting temperatures cause deposit formation, slagging, and sintering, which lead to problems during combustion [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the quality of these fuels is lower than wood biomass. The main problems are their low bulk density, high ash content, low ash melting temperatures, and low calorific values [5,6]. High ash content and low ash melting temperatures cause deposit formation, slagging, and sintering, which lead to problems during combustion [7].…”
Section: Introductionmentioning
confidence: 99%
“…Various types of straw, cereals, grasses, and seeds, which are low in Ca and high in Si and K, have an initial ash melting point significantly lower than wood fuels [10,11]. Zhai et al [12] Fire 2023, 6 identified the irregular aggregation of KCl, K 2 SO 4 , and other fusible matters as the main factor affecting the ash fusion of wheat straw and corn straw pellets. The ash completely melted at 1300 • C, and the Si, MgO, and CaO contents increased and formed low-meltingpoint eutectics.…”
Section: Introductionmentioning
confidence: 99%
“…Biomass and especially waste dendromass is one of the solid fuels within renewable energy sources. Today it often replaces fossil fuels used in heating plants producing heat and hot water for households (Plešingerová et al 2020;Nosek et al 2021). In recent years, however, attention has focused not only on the production of biopellets and other fuel products based on dendromass, but also on research into the disintegration of dendromass through its pretreatment and hydrolysis, especially enzymatic hydrolysis (Wang et al 2013;Pažitný et al 2020a and2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Among these, different kinds of biomass stand out, like agricultural crop residues [9][10][11][12], agroindustrial residues [13][14][15], forest biomass [16] and wood processing industry residues [17,18]. Other wastes benefit from this advantageous method of valorization, such as sewage sludge [19][20][21] or waste paper [22]. CFP could become a green energy source based on its close composition to wastepaper.…”
Section: Introductionmentioning
confidence: 99%